51. ULTRASOUND-GUIDED SUPRAINGUINAL FASCIA ILIACA BLOCK WITH ROPIVACAINE FOR HIP REPLACEMENT SURGERY (Vietnam Journal of Community Medicine, 2025)
Objective: To evaluate the analgesic effect of ultrasound-guided supra-inguinal fascial iliaca block with Ropivacaine for hip replacement surgery. At the same time, we review some undesirable effects of this method.Subjects and methods: A descriptive study was conducted on 30 patients with indications for hip replacement surgery, ASA I-III, at Viet Duc Univesity Hospital from February 2024 to December 2024. Patients were anesthetized above the supra-inguinal fascial iliaca block under ultrasound guidance, bolused with 20 ml of 0.25% Ropivacaine, then maintained with 0.1% Ropivacaine via an autobolus intermittent pump every 6 hours, 20 ml each time.Results: The average anesthesia technique time was 11.43 ± 5.5 mins. The pain relief effect was good with VAS scores < 4 at most study times, both at rest and during movement. No cases of side effects such as hypotension, respiratory failure, vomiting, nausea, urinary retention or local anesthetic toxicity were recorded. There was mild quadriceps weakness (average Bromage score 1.13 ± 0.35).Conclusion: The method of ultrasound-guided supra-inguinal fascial iliaca block, using Ropivacaine with a programmed autobolus intermittent mode, has good analgesic effect on patients after hip replacement surgery. This method is safe, does not affect hemodynamics and respiration, has few side effects, and allows for a reduction in the dose of anesthetic.
Keywords: Supra-inguinal fascial iliaca block, hip replacement, postoperative pain relief, Ropivacaine, ultrasound.